PERTIMBANGAN HAKIM DALAM MENGABULKAN JUSTICE COLLABORATOR TERHADAP TERDAKWA YANG MELAKUKAN TINDAK PIDANA KORUPSI - Nyimas Maharani Putri Pertiwi Zainudin Hasan (Universitas Muhammadiyah Metro, 2022)
The perpetrators of these criminal acts of corruption tried to cover up their crimes by all means and even made scenarios so that their crimes were difficult to identify by investigators and the prosecutor's office as the body authorized to conduct investigations in cases of corruption. Because the perpetrators of these crimes are difficult to identify, it is very effective if law enforcers invite the defendants of the corruption crime to reveal who are the other defendants and the mastermind behind the corruption and become a Justice Collaborator. The problem in the study is how the procedure for the defendant who commits a criminal act of corruption to apply as a justice collaborator, how the defendant returns state losses due to corruption committed by the defendant and how the judge's consideration in granting the application for justice collaborator against the accused of corruption. The research method used in this study is a normative juridical approach, namely an approach through library research, comparative studies and document studies by reading, quoting, and examining the rules or regulations related to the problem to be discussed and the empirical approach, namely collecting data. based on the results of direct interviews with resource persons who will relate to the problems that exist in this research. The results of the study show how the defendant who commits a criminal act of corruption to apply as a justice collaborator. The defendant can apply as a justice collaborator if the defendant is not the main actor in the case. The judge's consideration in granting the defendant's justice collaborator application, the judge considered several aspects including the defendant being able to cooperate cooperatively and in good faith during the trial, not covering up and witness testimony in line with what was explained by the defendant.